Visual Behavior Impairments as an Aberrant Sensory Processing in the Mouse Model of Fragile X Syndrome - Felgerolle, Chloé; Hébert, Betty; Ardourel, Maryvonne; Meyer-Dilhet, Géraldine; Menuet, Arnaud; Pinto-Morais, Kimberley; Bizot, Jean-Charles; Pichon, Jacques; Briault, Sylvain; Perche, Olivier (Frontiers in Behavioral Neuroscience, 2019)
Fragile X Syndrome (FXS), the most common inherited form of human intellectual disability (ID) associated to autistic-like behaviors, is characterized by dys-sensitivity to sensory stimuli, especially on the visual part. In absence of FMRP, both retinal and cerebral structures of the visual pathway are impaired, suggesting that perception and integration of visual stimulus are altered. However, the behavioral consequences of such defects remain unknown. In this study, carried out with male Fmr1-/y mice, we aimed to further define visual disturbances from a behavioral point of view by focusing on three traits characterizing visual modality: perception of depth, contrasts and movements. We performed specific tests (Optomotor Drum, Visual Cliff) to evaluate these visual modalities, their evolution from youth to adulthood, and to assess their involvement in a cognitive task. We show that Fmr1-/y mice exhibit alteration in their visual skills, displaying an impaired perception of perspective, a drop in their ability to understand a moving contrasted pattern, and a defect in their contrasts discrimination. Interestingly, these Fmr1-/y phenotypes remain stable over time from adolescence to late adulthood. Besides, we show that color and shape are meaningful for the achievement of a cognitive test involving object recognition. All together, these results underline the significance of visual behavior alterations in FXS conditions and how relevant it is to assess visual skills in neuropsychiatric models before performing behavioral tasks, such as cognitive assessments, that involve visual discrimination.